Perspectiva evolutiva de las tradicionales parejas de hecho frente a las uniones intersexuales - Muñoz Catalán, Elisa (Nómadas. Critical Journal of Social and Juridical Science, 2015)
Analyze the legal basis for the frequent today fact unions, the origin of these practices and their consequences for the juridical Order, taking as a starting point regulation of Roman law, mean deepen in an area which may be unknown if we remember that we are in a period in which the potential crisis of the traditional family is defended. In this sense, with the accomplishment of the writing that follow we pretend to investigate how the absence of the essential requirements, particularly the legal capacity or conubium, impacted on extramarital affairs and what was, in short, the reason of the prohibitions for the called from classical Roman legal as iustum matrimonium, against the roman marriage with full effects. Reasons for applying, throughout our intervention, we will defend six classificatory criteria to be used to group the great number of extramarital unions that existed, among which include: concubinage, illegal cohabitation, homosexuality, incestuous, simulated or between absent marriage, the unions with subjects who lacked physical capacity, adultery or prostitution; to finish, ultimately, with a brief mention of the ideological influence of the different emperors, the Christianity and the new regulations on intersex relations in Europe.